2021
DOI: 10.32615/ps.2021.020
|View full text |Cite
|
Sign up to set email alerts
|

Multi-colour fluorescence imaging of photosynthetic activity and plant stress

Abstract: Ivana Štětinová, Prague, for their decision to publish a special issue on fluorescence imaging of plants and also my colleague Roland Valcke, Diepenbeek, Belgium, the editor of this special issue, for his encouraging and valid endeavors to edit this issue. In addition, I thank Claus Buschmann, Karlsruhe, a former member of my group, for his valid help during the preparation of several figures and for reading the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Chl fluorescence is also used to detect and characterize abiotic and biotic stress responses (Guidi and Degl'Innocenti, 2012) and for phenotyping during breeding/selection of new stress resistant and/or higher yielding crops or microalgae (Chaerle et al, 2009; Pérez‐Bueno et al, 2019). It has also been extended to cover spatial resolution by fluorescence imaging (Johnson et al, 2009; Nedbal and Whitmarsh, 2004) which – depending on the resolution achieved ‐ allows to differentiate between macroscopic and/or microscopic variations in the fluorescence of a leaf related to differences in Chl responses, stress conditions (Lichtenthaler, 2021; Moustakas et al, 2021) or to variations in chloroplast structure at the subcellular level (Wientjes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chl fluorescence is also used to detect and characterize abiotic and biotic stress responses (Guidi and Degl'Innocenti, 2012) and for phenotyping during breeding/selection of new stress resistant and/or higher yielding crops or microalgae (Chaerle et al, 2009; Pérez‐Bueno et al, 2019). It has also been extended to cover spatial resolution by fluorescence imaging (Johnson et al, 2009; Nedbal and Whitmarsh, 2004) which – depending on the resolution achieved ‐ allows to differentiate between macroscopic and/or microscopic variations in the fluorescence of a leaf related to differences in Chl responses, stress conditions (Lichtenthaler, 2021; Moustakas et al, 2021) or to variations in chloroplast structure at the subcellular level (Wientjes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overgrazing can threaten the conservation of ecosystems through excessive defoliation or trampling of vegetation. It also indirectly increases the effect on soil structure (8,9). This leads to the acceleration of desertification processes (10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a previous study reported that the exposure of Arabidopsis to salt stress resulted in a decline in chlorophyll content [29], which also could be a result of the increase of F460 and F520 since the reabsorption of blue-green fluorescence is reduced [39]. The chlorophyll-fluorescence emission spectra usually exhibits two emission maxima around 690 nm and 740 nm, which are termed F690 and F740 [40,41]. The decrease of F690 is partially caused by the in vivo chlorophyll (overlapping of absorption and fluorescence emission bands of chlorophyll a forms) [42,43].…”
Section: Effect Of Salt Stress On Basic Fluorescence Parameters Of Arabidopsis Leavesmentioning
confidence: 99%